Technical assessment report on Jaweta Fish Farms Ltd Kenya - Mengistu, Samuel; Attia, Sameh (WorldFish, 2025)
In March 2025, WorldFish conducted a comprehensive technical and biosecurity assessment of Jaweta Fish Farms Ltd, located in Homa Bay County, Kenya, as part of the Climate-Resilient Aquaculture Systems for Africa (CASA) Project. The evaluation aimed to determin the farm’s readiness to receive and manage Genetically Improved Farmed Tilapia (GIFT) fry. The assessment was conducted by WorldFish scientists Dr. Samuel Bekele Mengistu and Dr. Sameh Attia through on-site visits, technical meetings, and a standardized evaluation framework.